Temporal Features-Fused Vision Retentive Network for Echocardiography Image Segmentation - Zhicheng Lin; Rongpu Cui; Limiao Ning; Jian Peng (Sensors)
Echocardiography is a widely used cardiac imaging modality in clinical practice. Physicians utilize echocardiography images to measure left ventricular volumes at end-diastole (ED) and end-systole (ES) frames, which are pivotal for calculating the ejection fraction and thus quantitatively assessing cardiac function. However, most existing approaches focus on features from ES frames and ED frames, neglecting the inter-frame correlations in unlabeled frames. Our model is based on an encoder–decoder architecture and consists of two modules: the Temporal Feature Fusion Module (TFFA) and the Vision Retentive Network (Vision RetNet) encoder. The TFFA leverages self-attention to learn inter-frame correlations across multiple consecutive frames and aggregates the features of the temporal–channel dimension through channel aggregation to highlight ambiguity regions. The Vision RetNet encoder introduces explicit spatial priors by constructing a spatial decay matrix using the Manhattan distance. We conducted experiments on the EchoNet-Dynamic dataset and the CAMUS dataset, where our proposed model demonstrates competitive performance. The experimental results indicate that spatial prior information and inter-frame correlations in echocardiography images can enhance the accuracy of semantic segmentation, and inter-frame correlations become even more effective when spatial priors are provided.